2021
DOI: 10.3389/fonc.2021.684867
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity and Safety of Penpulimab (Anti-PD-1) With Anlotinib as First-Line Therapy for Unresectable Hepatocellular Carcinoma: An Open-Label, Multicenter, Phase Ib/II Trial (AK105-203)

Abstract: ObjectiveThis study aims to assess the efficacy and safety of penpulimab (a humanized anti-PD-1 IgG1 antibody) with anlotinib in the first-line treatment of Chinese patients with uHCC.MethodsIn this open-label multicenter phase Ib/II trial, patients with histologically or cytologically confirmed uHCC, without previous systemic treatment, aged 18–75 years old, classified as BCLC stage B (not amenable for locoregional therapy) or C, with Child–Pugh score ≤7 and ECOG performance status ≤1 were enrolled. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 32 publications
6
28
2
Order By: Relevance
“…Sintilimab plus anlotinib had an ORR of 35.0% per RECIST v1.1, which is consistent with other combination regimens of an ICI and an antiangiogenic TKI such as in the KEYNOTE-524 trial ( 18 ), the RESCUE trial ( 26 ), and the AK105-203 trial ( 29 ), which achieved an ORR between 31% and 36%. Meanwhile, sintilimab plus bevacizumab in the ORIENT-32 study had an ORR of 20.0% and atezolizumab plus bevacizumab yielded an ORR of 27.3% in the milestone IMbrave150 study ( 16 , 30 ), suggesting that small molecule inhibitors of oncoangiogenesis might be more effective than antiangiogenic monoclonal antibodies in enhancing patient treatment response when in combination with an ICI.…”
Section: Discussionsupporting
confidence: 80%
“…Sintilimab plus anlotinib had an ORR of 35.0% per RECIST v1.1, which is consistent with other combination regimens of an ICI and an antiangiogenic TKI such as in the KEYNOTE-524 trial ( 18 ), the RESCUE trial ( 26 ), and the AK105-203 trial ( 29 ), which achieved an ORR between 31% and 36%. Meanwhile, sintilimab plus bevacizumab in the ORIENT-32 study had an ORR of 20.0% and atezolizumab plus bevacizumab yielded an ORR of 27.3% in the milestone IMbrave150 study ( 16 , 30 ), suggesting that small molecule inhibitors of oncoangiogenesis might be more effective than antiangiogenic monoclonal antibodies in enhancing patient treatment response when in combination with an ICI.…”
Section: Discussionsupporting
confidence: 80%
“… 24 Besides, penpulimab (a humanized anti-PD-1 antibody) plus anlotinib demonstrated an ORR of 31.0%, a DCR of 82.8%, and a median PFS of 8.8 months (95% CI, 4.0–12.3) after the first-line treatment in Chinese patients with unresectable HCC. 25 In the present study, anlotinib and PD-1 blockades combination therapy resulted in an encouraging ORR of 28.57% and a DCR of 71.43%, which was comparable to previously combination therapy or PD-1/PD-L1 monotherapy. However, anlotinib and PD-1 blockade combination therapy in our study not tended to yield a favorable efficacy than anlotinib monotherapy in terms of ORR, DCR, PFS, and OS (all p >0.05).…”
Section: Discussionsupporting
confidence: 79%
“… 23 Although several phase II studies have confirmed the clinical benefit of anti-PD-1 monotherapy (sintilimab or penpulimab) plus anlotinib for advanced or unresectable HCC, both studies were performed in the first-line setting. 24 , 25 Evidence of anlotinib combined with anti-PD-1 monotherapy as second-line or further therapy in advanced HCC is still scanty currently, especially in the real-world setting. Thus, a retrospective, real-world study was conducted to evaluate the effectiveness and safety of anlotinib with or without PD-1 blockades as first-line or further therapy for Chinese patients with advanced primary HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In 31 patients evaluated based on the RECIST 1.1 criteria, the first-line treatment of hepatocellular carcinoma with anlotinib in combination with penpulimab achieved an overall response rate (ORR) of 31%, a disease control rate (DCR) of nearly 83%, and a median progression-free survival (PFS) of 8.8 months, which was comparable to the efficacy of similar anti-angiogenic therapy and immunotherapy combinations. Adverse effects were manageable, and the safety profile was deemed satisfactory ( 11 ). Similarly, studies on the treatment of ES-SCLC have repeatedly reported the clinical benefits of this drug combination approach.…”
Section: Introductionmentioning
confidence: 99%